The physiological, neuromuscular, and perceptual response to even- and variable-paced 10-km cycling time trials - Veneman, T.; Schallig, W.; Eken, M.; Foster, C.; de Koning, J. J. (International Journal of Sports Physiology and Performance, 2021)
Background: During self-paced (SP) time trials (TTs), cyclists show unconscious nonrandom variations in power output of up to 10% above and below average. It is unknown what the effects of variations in power output of this magnitude are on physiological, neuromuscular, and perceptual variables.